A fast and high throughput LC-MS/MS method for the determination of 58 human and veterinary drugs in river water. Issue 29 (17th July 2017) - Chen, Xiao-Hong; Zhao, Yong-Gang; Qiu, Qiao-Li; Zhu, Yan; Min, Jian-Qing; Jin, Mi-Cong
Abstract : This study developed a method to perform the simultaneous determination of 58 (ultra) trace human and veterinary drugs in river water. Abstract : This study developed a method to perform the simultaneous determination of 58 (ultra) trace human and veterinary drugs in river water. The analytes included 24 steroid hormones, 22 sulfonamides and 12 quinolones. The easy-to-handle magnetic dispersive solid-phase extraction (Mag-dSPE) procedure was performed using three-dimensional interconnected magnetic chemically modified graphene oxide (3D-Mag-CMGO) as the adsorbent, and an enrichment factor of 100 times was obtained. Under the optimal conditions, the results showed higher extraction capacity of 3D-Mag-CMGO with recoveries between 78.0 and 109%. The limits of quantification (LOQs) for 58 (ultra) trace analytes are in the range of 0.10–2.09 ng L −1 . Validation results on linearity, specificity, accuracy, and precision, as well as the application to the analysis of 58 (ultra) trace analytes in ten real samples demonstrated the applicability to environment monitoring analysis.